2022
DOI: 10.2147/dddt.s371506
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Dose of Dapagliflozin Improves Cardiac Outcomes by Normalizing Mitochondrial Fission and Reducing Cardiomyocyte Apoptosis After Acute Myocardial Infarction

Abstract: Dapagliflozin (DAPA) has been reported to have significant cardiac protective effects on heart failure (HF). However, the dose and time, as well as the underlying mechanisms, for DAPA treatment in acute myocardial infarction (AMI) remain controversial. The aim of this study aimed to assess the efficacy and safety of DAPA treatment along with an increased concentration gradient for AMI and explore the potential mechanisms. Methods: Non-diabetic Sprague-Dawley rats were used for establishing AMI models and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 48 publications
0
11
1
Order By: Relevance
“…Long-standing diabetes may cause several complications including diabetic neuropathy, diabetic nephropathy, diabetic retinopathy, and macrovascular complications. These complications may have an adverse impact on the quality of life of the diabetic population and result in elevated morbidity and mortality [39].…”
Section: Resultsmentioning
confidence: 99%
“…Long-standing diabetes may cause several complications including diabetic neuropathy, diabetic nephropathy, diabetic retinopathy, and macrovascular complications. These complications may have an adverse impact on the quality of life of the diabetic population and result in elevated morbidity and mortality [39].…”
Section: Resultsmentioning
confidence: 99%
“…A meta‐analysis of these preclinical investigations found that SGLT2 inhibitors decrease myocardial infarct size, independent of T2DM 30 . Dapagliflozin has been found to ameliorate cardiac function, remodelling, myocardial apoptosis, and inflammatory cytokines, normalize mitochondrial fission, and modulate macrophage polarization via STAT3 signalling in MI 31–33 . Empagliflozin directly impedes the Na + /H + exchanger 1 in cardiomyocytes to suppress autophagic cell death in MI mice 34 .…”
Section: Discussionmentioning
confidence: 99%
“…30 Dapagliflozin has been found to ameliorate cardiac function, remodelling, myocardial apoptosis, and inflammatory cytokines, normalize mitochondrial fission, and modulate macrophage polarization via STAT3 signalling in MI. [31][32][33] Empagliflozin directly impedes the Na + /H + exchanger 1 in cardiomyocytes to suppress autophagic cell death in MI mice. 34 Moreover, SGLT2 inhibitors alleviate reperfusion injury, [35][36][37] boost endothelial function, orchestrate myocardial energy metabolism, and attenuate oxidative stress pathways to augment coronary blood flow.…”
Section: Grade Of Evidencementioning
confidence: 99%
“…Various approaches such as pharmacologic interventions and stem cell therapy have been shown to attenuate AVR after AMI. 10,11 Cell transplantation is a new therapeutic option for AMI and has attracted increasing interest from scholars. 12 The easy availability of large quantities makes bone marrow-derived mononuclear cells reliable and attractive donor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Various approaches such as pharmacologic interventions and stem cell therapy have been shown to attenuate AVR after AMI. 10,11…”
Section: Introductionmentioning
confidence: 99%